Avaliação das condições de cultivo na fotofermentação da microalga Chlamydomonas reinhardtii - Sousa, Letícia de Moura (2016)
Regarding the current scenario of fossil fuels depletion, climate change, high oil prices coupled with political, economic and environmental conflicts, the investigation of sustainable technologies for energy production became necessary. In this contest, biofuel (ethanol) synthesis from microalgae has been highlighted. The green alga Chlamydomonas reinhardtii under anaerobic conditions and associated with other micro-organisms have been investigated. In the current work, cultures of C. reinhardtii were submitted to fermentations using bioreactors (50 mL and 1.5 L of capacity) at 25 °C and 12-hour photoperiod, under operational conditions such as sulphur (TAP-S medium) and acid acetic (TAP-AC medium) depletions. The influence of mixotrophic carbon sources and the use of effluent from the bacterium photo-fermentation (hybrid system) were also verified. The findings in low scale (50 mL) showed that green alga cultivated in basal medium Tris Acetate Phosphate (TAP) did not result in ethanol production, since glucose and lactose from milk whey permeate (MWP) have been added, both at 1 g/L. Although, TAP-S medium supplemented with carbon sources resulted in ethanol production, being 1189.91 mg/L maximum ethanol concentration observed in low scale. In the following, TAP medium supplemented with three different sources of lactose was evaluated, being MWP (70 % lactose), MW (50 % lactose) and lactose PA, at initial concentration adjusted to 5 g/L. The ethanol production occurs in all cases. Maximum volumetric productivity was 2.31 mmol ethanol/L.day. It was verified in the medium supplement with MWP. In TAP-S and TAP-AC media the ethanol production was negligible, even with carbon source addition. To hybrid system, the result in low scale showed ethanol production in the presence of glucose and MWP, added alone for the photosynthetic bacterium (Rhodobacter capsulatus) medium (metabolized RCV) at 5 g/L. However, the highest ethanol production (1357 mg/L) was observed in the 1.5 L reactor, adding refreshed medium supplemented with MWP every 48 hours.